Patrimonio alimentario y gastronómico del cantón Pangua de la provincia de Cotopaxi. - Chango Alulema, María José (2022)
The current research deals about the Food and Gastronomic Heritage of the Pangua canton, Cotopaxi province, it should be noted, what this area has an important cultural heritage, but is currently found threatened, due to the social processes, which society must adapt. Thus, the study has a qualitative approach, for this, it was taken up the theoretical-methodological contributions, since it was collected data, in order to arrive at the got results interpretation in historical, social, cultural aspects directly related to the gastronomy in the study area. Thus, in the first aim, it was made the compilation both primary and secondary, through bibliographic information, through the search and documentation review (scientific articles, magazine articles, books), what are found in the Google school bibliographic manager; the review PDOT for the 2018 and 2020 years, both the canton and each parish, official web pages of each parish GAD, which showed that agriculture is one the main economic activities, where the cocoa, sugar cane, beans and banana production are the most cultivated products per hectare, because they provide excellent economic returns. Regarding the cultural manifestations, the Pangüense Reunion is the festival, what identifies each site native, because on these dates all those people, who emigrated to other cities return to Pangua, commemorating the family reunion and at the same time, it is present gastronomy, because there are events where events, where it was evidenced the different cultures gastronomic fusion. For the second aim, using the ethnographic method and the INPC methodology, the were applied the informant mapping technique and the snowball technique to determine key informants (authorities, street vendors, housewives, farmers), for this, it was made 8 field trips to each parish from Pangua canton, where the participant allowed and the performance 20 interviews with the key informants, with the semi-structured questions guide and the INPC field 4 file, gastronomy sub-field, which allowed the 11 food heritages and 16 gastronomic heritages identification; which the lamb tripe sancocho has greater sensitivity to change, but the common thing among them is. what they have been inherited from parents to children. In the third aim, the was applied the holistic method, since its way seeing things appreciates their entirety, without reducing them to their integral parts, thus, allowing the organization and analysis the most relevant data the proposal an academic article, with the purpose that it will serve as a dissemination instrument to revalue the food and gastronomic heritage in the territory, in turn, strengthening the cultural diversity from Cotopaxi Province.